Renoprotective Effect of Agmatine Against Cyclosporin A- Induced Nephrotoxicity in Rats - El-Kahef, Dalia Hassan; El-kenawi, Asmaa; Suddek, Ghada; Salem, Hatem (Fakultas Farmasi, Universitas Gadjah Mada, 2018)
In this study, the modulator effect of agmatine on the oxidative nephrotoxicity of cyclosporin Â (CsA) Â in the kidneys of rats was investigated by determining indices of lipid peroxidation and the activities of antioxidant enzymes, as well as by histological analyses. Furthermore, the effect of agmatine on CsA induced hypersensitivity of urinary bladder rings to ACh was estimated. Twenty-four male Sprague-Dawley rats were randomly divided into three groups, namely control, CsA and CsA plus agmatine. At the end of the study, all rats were sacrificed and then blood, urine samples and kidneys were taken. CsA administration caused a severe nephrotoxicity which was evidenced by an elevation of serum creatinine, blood urea nitrogen, serum lactate dehydrogenase and protein in urine with a concomitant reduction in serum albumin and creatinine clearance as compared with the controls. Moreover, a significant increase in renal contents of malondialdehyde, myeloperoxidase and tumor necrosis factor-alpha together with a significant decrease in renal reduced glutathione, superoxide dismutase activities and nitric oxide content was detected upon CsA administration with increasing the sensitivity of isolated urinary bladder rings to ACh. Agmatine protected kidney tissue against the oxidative damage and the nephrotoxic effect caused by CsA treatment.Â In addition, agmatine significantly reduced the responses of isolated bladder rings to ACh. The results from our study indicate that agmatine supplement attenuates CsA -induced renal injury via the amelioration of oxidative stress and inflammation of renal tubular cells. Exposure to CsA caused vacuolated tubular cells and thickened wall vessels, which was found to be prevented by agmatine concurrent treatment. Our study indicates that agmatine administration with CsA attenuates oxidative-stress associated renal injury by reducing oxygen free radicals and lipid peroxidation and inhibiting inflammatory mediators such as TNF-Î±.Keywords: CsA; Agmatine; Nephrotoxicity; Urinary bladder; TNF-Î±; Nitric oxide